A note on fuzzy PS-ideals in PS-algebra and its level subsets - Thirugapillai, Priya; Chandran, Rama (International Journal of Advanced Mathematical Sciences, 2014)
In this paper, a new notion, named fuzzification of PS – Algebra, which is a generalization of BCK/BCI/TM/BH/Q/d/KU-algebras, is introduced, along with PS-ideal and we have discussed some of their properties in detail. Keywords: PS-Algebra, PS-ideal, Fuzzy PS-Ideal, Level Subsets, PS-Subalgebra and Fuzzy PS-Subalgebra.